The villain virus eaudiobook - Buckley, Michael (N.E.R.D.S., 2012)
New York Times best-selling author Michael Buckley has created another hit series with his riotously popular NERDS books. In this fourth installment, the Villain Virus is turning people into evil masterminds bent on world domination. Former NERDS member Heathcliff Hodges is to blame, and to stop him, Flinch will have to miniaturize himself and travel inside Heathcliff's body to the virus' source. But it won' t be easy fighting his way past white blood cells, putrid stomach acid, and a pack of nasty nanobytes.